CONTABILIDADE DE CUSTOS ECOLÓGICOS COMPLETOS NO CONTEXTO DA SUSTENTABILIDADE - Satolo, E. G.; Simon, A. T.; Calarge, F. A.; Braga Junior, S. S. (Revista Brasileira de Engenharia de Biossistemas, 2014)
In the last decade, sustainability has emerged as one of the main issues addressed in academic research. This matter has also involved companies and their activities in the social, environmental and financial scope. However, while companies have started showing greater interest in preserving the environment and in considering social aspects, the measurement of involved costs has not been an easy task. The concept of Complete Ecological Cost Accounting (CECA) is a tool that intends to measure the costs in a comprehensive manner, integrating traditional accounting and so-called social-environment accounting. This article aims to make a critical analysis of the CECA model and proposes guidelines for its improvement. The focus is to suggest a complementation of the model by integrating parameters to collect data and assess results from a qualitative and quantitative point of view, thereby allowing companies to evaluate their level of maturity as it relates to socio-environmental issues.